Postcesarean Thromboprophylaxis with Two Different Regimens of Bemiparin - Milagros Cruz; Ana M. Fernández-Alonso; Isabel Rodríguez; Loreto Garrigosa; Africa Caño; Pilar Carretero; Amelia Vizcaíno; Amanda Rocío Gonzalez-Ramirez (Obstetrics and Gynecology International)
Objectives. To compare the effectiveness of postcesarean thromboprophylaxis with two different regimens of bemiparin. Material and Methods. The study included 646 women with cesarean delivery in our hospital within a 1-year period, randomly assigned to one of two groups for prophylaxis with 3500 IU bemiparin once daily for 5 days or 3500 IU bemiparin once daily for 10 days. Results. There was one case of pulmonary embolism (first day following cesarean). An additional risk factor was present in 98.52% of the women, most frequently emergency cesarean, anemia, or obesity. The only risk factors for thromboembolic disease significantly related to pulmonary thromboembolism were placental abruption and prematurity. There were no differences in thromboembolic events among the two thromboprophylaxis regimens. Conclusions. Cesarean-related thromboembolic events were reduced in our study population due to the thromboprophylactic measures taken. Thromboprophylaxis with 3500 IU bemiparin once daily for 5 days following cesarean was sufficient to avoid thromboembolic events.